(NmAJSKAQ NO^X(B.s - (Nn(B.(Na(B.(NrIMSKOGO(B- (NkORSAKOWA(B.s ((NmOSKWA s (NgOSUDARSTWENNOE MUZYKALXNOE IZD(B.s, 1959)
(NmAJSKAQ NO^X(B-(NWTORAQ IZ PQTNADCATI OPER nIKOLAQ aNDREEWI^A rIMSKOGO(B-(NkORSAKOWA(B.s
Keywords: (NLIBRETTOs